Cyanide-Mediated Synthesis of Sulfones and Sulfonamides from Vinyl Sulfones - Roy, Tamal; Lee, Ji-Woong (Synlett, 2020)
We report a facile synthesis of sulfones, β-keto sulfones, and sulfonamides from vinyl sulfones via an addition–elimination sequence where in situ generation of nucleophilic sulfinate ion is mediated by cyanide. The use vinyl sulfones renders high selectivity for S-alkylation to produce sulfones in high yields. In the presence of N-bromosuccinimide, primary and secondary amines underwent sulfonamide formation. A preliminary mechanistic study showed the formation of acrylonitrile as an innocent byproduct, without interfering with the desired reaction pathway while generating a sulfinate nucleophile.
Keywords: cyanide; sulfonate; sulfones; sulfonamides; vinyl sulfones